2023
DOI: 10.1002/inmd.20220013
|View full text |Cite
|
Sign up to set email alerts
|

Facing inevitable PARPis resistance: Mechanisms and therapeutic strategies for breast cancer treatment

Abstract: BRCA1/2 gene mutations, which result in a dysfunction of homologous recombination repair, have been discovered in at least 5% of breast cancer (BC) patients with the increase in BC incidence in recent years. PARP inhibitors (PARPis), the first drugs with clinical approval based on synthetic lethality, have been approved to treat BRCA1/2-mutant BC. However, as with other targeted drugs, PARPis drug resistance has become a significant obstacle in the application of PARPis. In this paper, we discuss the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 109 publications
0
1
0
Order By: Relevance
“…However, factors such as intratumor heterogeneity, adaptive mutations, epigenetic alterations, and metabolic changes enable some cancer cells to withstand clinical doses of medications, thereby escalating the challenge of medication resistance in cancer treatment ( Vasan et al, 2019 ). Investigating the molecular mechanisms of drug resistance is crucial for improving therapeutic outcomes and introducing new treatment strategies ( Nussinov et al, 2021 ; Liu et al, 2023b ). Previous research revealed that oncogene-transformed mouse embryonic fibroblasts developed increased resistance to chemotherapeutic agents like methotrexate, gemcitabine, and etoposide, due to alterations of Per2 gene.…”
Section: The Per Gene Family and Cancer Therapymentioning
confidence: 99%
“…However, factors such as intratumor heterogeneity, adaptive mutations, epigenetic alterations, and metabolic changes enable some cancer cells to withstand clinical doses of medications, thereby escalating the challenge of medication resistance in cancer treatment ( Vasan et al, 2019 ). Investigating the molecular mechanisms of drug resistance is crucial for improving therapeutic outcomes and introducing new treatment strategies ( Nussinov et al, 2021 ; Liu et al, 2023b ). Previous research revealed that oncogene-transformed mouse embryonic fibroblasts developed increased resistance to chemotherapeutic agents like methotrexate, gemcitabine, and etoposide, due to alterations of Per2 gene.…”
Section: The Per Gene Family and Cancer Therapymentioning
confidence: 99%